2012
DOI: 10.1128/aem.07180-11
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Modified Charcoal-Cefoperazone-Deoxycholate Agar by Supplementation with a High Concentration of Polymyxin B for Detection of Campylobacter jejuni and C. coli in Chicken Carcass Rinses

Abstract: Modified charcoal-cefoperazone-deoxycholate agar (mCCDA) was improved by supplementation with a high concentration of polymyxin B. The ability of the supplemented medium to isolate Campylobacter jejuni and C. coli from chicken carcass rinses was compared to that of Campy-Cefex agar and mCCDA. Modification of mCCDA with increased polymyxin B yielded a significantly (P < 0.05) higher isolation rate and greater selectivity than those achieved using Campy-Cefex agar and mCCDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
(14 reference statements)
2
32
0
Order By: Relevance
“…Chon et al (2012) reported that the addition of polymyxin B restored some of the mCCDA medium's selectivity for Campylobacter and inhibited E. coli; however resistance could develop over time (Urban et al, 2011). In contrast our approach of adding the tazobactam β-lactamase inhibitor circumvents this potential problem as no additional antimicrobial is used; rather the compound is simply restoring the efficacy of cefoperazone against ESBL-producing organisms by competitive inhibition.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Chon et al (2012) reported that the addition of polymyxin B restored some of the mCCDA medium's selectivity for Campylobacter and inhibited E. coli; however resistance could develop over time (Urban et al, 2011). In contrast our approach of adding the tazobactam β-lactamase inhibitor circumvents this potential problem as no additional antimicrobial is used; rather the compound is simply restoring the efficacy of cefoperazone against ESBL-producing organisms by competitive inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…coli grows more rapidly (24h) under the same incubation conditions used for the isolation of Campylobacter (37-42°C; 5-10% O 2 ; 10% CO 2 , 48h) (Chon et al, 2013). Previous researchers have tried various methods to remove ESBL E. coli contamination on various Campylobacter selective media (Chon et al, 2012;Moran et al, 2011;Jasson et al, 2009). Some success has been achieved at inhibiting ESBL E. coli and restoring selectivity for Campylobacter with β-lactamase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 80 whole chickens were purchased from October 2011 to February 2012 from grocery stores in Seoul, South Korea. All experimental procedures for detecting C. jejuni and C. coli were performed in accordance with our previous study with minor modification (Chon and others ). The chicken carcasses were rinsed with 400 mL of buffered peptone water (Difco, Sparks, M.D., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%